Psychological basis of eliminating frustration situations in adolescent football players - Egamberdiev Farkhod Tukhtayevich (THE INNOVATION ECONOMY, 2026)
The article analyzes the reasons why adolescent football players encounter frustrating situations, the psychological impact of these situations, as well as effective psychological approaches to their elimination. The author substantiates the role of cognitive-behavioral, emotional control and social support systems in overcoming frustration. The results of the article are of great importance in the practice of sports psychology, especially in work ing with adolescents.